Opinion formation in social networks with neighbourhood stimulations - Lee, Wai Hong (2019)
Opinions are formed as we gain information throughout our daily life. We gain valuable information through radio broadcasting, television, communication, and when meeting someone new. Unknowingly people create an opinion on everything in their daily life. Having these thoughts of “maybe” is also a form of opinion as it is considered being in the centre. Studies on opinion started from the field of sociology. During these few years, there have been an accelerated in development and more common use of the Internet. The internet has become a platform for people to exchange information, and it is a place where people express their thoughts and emotions. The need to research on network topology will help in understanding more about opinion formation in terms of how they communicate and form bonds. This report describes the study on opinion formation in complex social systems and if it would be affected if there exists a neighbourhood stimulation. This study will also include whether the existence of such stimulations would encourage extreme opinions to emerge, or maybe drive system opinion evolution in a certain way. Firstly, the studies on Erdős-Rényi Network Model and Barabasi-Albert Network Model will be an opinion formation simulation. Next, the studies of Weisbuch-Deffuant model will be used to understand the interaction between networks. The study will be carried out mainly by doing simulation written in Python language and using the Jupyter Notebook software. Its objective is mainly to research more about opinions in a social network.